The Effect of Date Fruit Consumption on Hemoglobin Levels among Adolescent Girls - Vina Nailalmuna; Nana Aldriana; Andria; Sri Wulandari (CV. AFDIFAL MAJU BERKAH, 2025)
Anemia is a common health problem among adolescent girls, primarily caused by menstruation and insufficient iron intake. One potential non-pharmacological intervention to increase hemoglobin levels is the consumption of date fruits (Phoenix dactylifera), which are rich in iron, vitamins, and other essential minerals. This study aims to determine the effect of date fruit consumption on hemoglobin levels among female adolescents at SMK Negeri 2 Kepenuhan, Rokan Hulu Regency. This research used a quantitative method with a pre-experimental design, specifically a one group pre-test and post-test. The sample consisted of 60 female students with hemoglobin levels below 12 g/dL who were not menstruating during the intervention. The intervention involved giving 7 dates daily for 5 consecutive days. Hemoglobin levels were measured before and after the intervention using the Easy Touch GCHb device. The results showed an increase in the average hemoglobin level from 10.87 g/dL before the intervention to 13.36 g/dL after the intervention. A paired t-test statistical analysis revealed a p-value of 0.001 (p < 0.05), indicating a significant difference between the pre- and post-intervention measurements. These findings suggest that regular consumption of date fruits can effectively raise hemoglobin levels. In conclusion, the consumption of date fruits has a significant effect on increasing hemoglobin levels in adolescent girls and can serve as a natural alternative for preventing anemia. This research is expected to provide a reference for developing school-based nutrition improvement programs, particularly in efforts to prevent anemia among adolescents.